A Mindlin multilayered hybrid-mixed approach for shell structures without shear correction factors. Issue 4 (3rd July 2016) - Tafla, Achraf; Zouari, Wajdi; Ayad, Rezak
Abstract : In this paper, we present two four-node multilayered hybrid-mixed shell elements for the static and free vibration analyses of plate and shell composite structures. Their formulation is based on the first shear deformation theory of Reissner/Mindlin without transverse shear correction factors. Linear and quadratic variations of the local in-plane and transverse shear stresses across the thickness, respectively, are supposed. To reduce the total number of variables in these models, transverse shear stresses are directly related to bending stresses by using two equilibrium equations. The performances of the proposed elements are assessed by means of two known numerical benchmarks and their results are found to agree globally well with the reference solutions.